The Armenians of Penang - Wright, Nadia H. ([Middle Park, Vic] : Entrepot Publishing and Amassia Publishing, 2018)
Why is there an Armenian Street in Penang? This quaint, narrow street draws visitors from around the world but there is little to explain the legacy of Penang’s small, bygone Armenian population, after which it was named. Nadia Wright has spent decades tracing the history of the Armenians in Southeast Asia. Civic-minded and skilled businessmen, they played a small but very significant role in the development of Penang, particularly in the 1800s. This is the story of some of the prominent Armenian personalities of Penang and of the fate of their tiny community.
In English.
Keywords: Armenians -- Malaysia -- Penang -- History